ANALISIS PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fadilla, Afra; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2013)
Research conducted aims to determine whether there is influence of Cash Position (CP), Debt to Equity Ratio (DER), and Return On Assets (ROA) partially or jointly against Dividend Payout Ratio (DPR) on the listed property company Indonesia Stock Exchange from 2008 to 2010. The results showed that of the three independent variables ROA and DER variables significantly influence the Dividend Payout Ratio while variable CP no significant effect on Dividend Payout Ratio. R-square value of 62.6%.